Peptide Receptor Radionuclide Therapy of Late-Stage Neuroendocrine Tumor Patients with Multiple Cycles of (177)Lu-DOTA-EB-TATE - Liu, Qingxing (J Nucl Med, 2021)
This study aimed to evaluate the safety and efficacy of multiple cycles of (177)Lu-DOTA-Evans blue (EB)-TATE peptide receptor radionuclide therapy (PRRT) at escalating doses in neuroendocrine tumors (NETs). Methods: Thirty-two NET patients were randomly divided into 3 groups and treated with escalating doses. Group A received 1.17 ± 0.09 GBq/cycle; group B, 1.89 ± 0.53 GBq/cycle; and group C, 3.97 ± 0.84 GBq/cycle. The treatment was planned for up to 3 cycles. Treatment-related adverse events were graded according to the National Cancer Institute Common Terminology Criteria for Adverse Events (CTCAE), version 5.0. Treatment response was evaluated according to the European Organisation for Research and Treatment of Cancer criteria and modified PERCIST. Results: Administration of PRRT was well tolerated, without life-threatening adverse events (CTCAE grade 4). CTCAE grade 3 hematotoxicity was recorded in 1 patient (16.6%) in group B (thrombocytopenia) and 3 patients (21.4%) in group C (thrombocytopenia in 3, anemia in 1). CTCAE grade 3 hepatotoxicity (elevated aspartate aminotransferase) was recorded in 1 patient in group A (8.3%) and 1 patient in group C (7.1%). No nephrotoxicity was observed. According to the criteria of the European Organisation for Research and Treatment of Cancer, the overall disease response rates were similar in groups A, B, and C (50.0%, 50.0%, and 42.9%, respectively), and the overall disease control rates were higher in groups B (83.3%) and C (71.5%) than in group A (66.7%). According to modified PERCIST, a lower disease response rate but a similar disease control rate were found. When a comparable baseline SUV(max) ranging from 15 to 40 was selected, the percentage change in SUV(max) increased slightly in group A (2.1% ± 40.8%) but decreased significantly in groups B and C (−38.7% ± 10.0% and −14.7% ± 20.0%, respectively) after the first PRRT (P = 0.001) and decreased in all 3 groups after the third PRRT (groups A, B, and C: −6.9% ± 42.3%, −49.2% ± 30.9%, −11.9% ± 37.9%, respectively; P = 0.044). Conclusion: Dose escalations of up to 3.97 GBq/cycle seem to be well tolerated for (177)Lu-DOTA-EB-TATE. (177)Lu-DOTA-EB-TATE doses of 1.89 and 3.97 GBq/cycle were effective in tumor control and more effective than 1.17 GBq/cycle.